Can stakeholders agree on how to reduce human–carnivore conflict on Namibian livestock farms? A novel Q-methodology and Delphi exercise. Issue 2 (25th January 2016) - Rust, Niki A.
Abstract: Conflict between carnivores and livestock farmers affects human livelihoods and predator populations. Historically, successful mitigation of this conflict has been limited, sometimes because of a lack of participation among stakeholders to create and implement agreeable and effective solutions. Finding common ground between stakeholders can, however, be difficult, partly because of the range and intensity of values held. Using a novel combination of Q-methodology and the Delphi technique, I investigated whether a diverse range of stakeholders could agree on how to mitigate conflict between carnivores and livestock farmers in Namibia. A strong consensus was reached on using conservation education and husbandry training to reduce livestock depredation. Two narratives emerged: one group preferred non-lethal methods to manage the conflict, whereas a smaller group preferred lethal measures. This new decision-making exercise has potential to be applied to other conservation conflicts to assist with participatory decision making.